Delayed linear difference equations: the method of Z-transform - Mahmudov, Nazim, I (Univ Szeged, Bolyai Institute, 2020)
A system of nonhomogeneous linear difference equations with linear parts given by non-commutative matrices is studied. Representation of its solution is derived by means of newly defined delayed perturbation of discrete matrix exponential using the Z-transform. We discard the invertibility condition of matrix of non delayed term used in recent works related to the representation of solutions for delayed linear difference systems.
Keywords: Z-transform; difference equations